¿Una fruta real ? Sobre un encuentro europeo con el ananá americano y su puesta en imagen* - Milena Gallipoli (Nuevo mundo - Mundos Nuevos, 2017)
The circulation of images and texts about America’s natural world was one of the keys in terms of the generation of new knowledge modalities regarding this fascinating and recently discovered new geography. This article proposes to explore the itineraries of a particular specimen of the American flora: the pineapple. The particularity of this fruit is that access to its knowledge has been channelled towards a multiplicity of courses, it has overflown the discipline of natural history and it has managed to proclaim itself as significant. Based on the analysis of a series of study cases of accounts about this fruit that were accompanied by images that appeared throughout a wide range of time (from the 16th to the 18th century) and a wide geographical scope, this work pretends to ponder on knowledge as experience and about the process of representation as expression of such knowledge.